The Effects of Three Step Interview Strategy Towards Students’ Speaking Ability - I Made Permadi Utama (Jurnal Paedagogy, 2018)
This research was aimed to know the positive effect of Three-Step-Interview strategy towards students’ speaking ability. The research was experimental research and was categorized quasi experimental especially nonequivalent control group design. The population of the research was the first semester students of hotel at Akademi Pariwisata Mataram consisting of six classes. Two classes were selected as the samples; those were IE and IF. They were drawn using cluster random sampling technique. Experimental group was treated using Three-Step-Interview strategy, and control group was treated using Think Pair Share strategy. The technique used for data collection was an interview. The result of the test was scored by speaking scoring rubric. Then, the scores were analyzed using t-test formula. According to the analysis, it showed that the value of to(t obtain)= 2.31 is higher than the value of tt (t table)= 2.00 at the level of significance of 5% and the degree of freedom (df) 58. Therefore, it can be concluded that there was significant difference between speaking scores of students taught by using value Three-Step-Interview strategy and taught by using Think Pair Share strategy. In other words, Three-Step-Interview strategy has positive effect towards the students’ speaking ability.